THE IMPORTANCE OF LEARNING FOREIGN LANGUAGES IN THE MODERN WORLD - Atham Ziyodullayev; Madina Neʼmatova Baxtiyor qizi (TADQIQOTLAR, 2025)
Abstract: This paper examines the importance of learning foreign languages in today’s globalized world. Foreign language competence enhances communication skills,  broadens  cultural  understanding,  and  increases  academic  and  professional opportunities.  The  study  explores  how  multilingualism  contributes  to  cognitive development, intercultural communication, and competitiveness in the international labor market. Additionally, it highlights the role of modern technologies and innovative teaching methods in the process of language learning. The findings emphasize that learning foreign languages is an essential requirement for successful integration into global society.